Thermosetting epoxy reinforced shape memory composite microfiber membranes: Fabrication, structure and properties. (September 2015) - Zhang, Fenghua; Zhang, Zhichun; Liu, Yanju; Cheng, Weilu; Huang, Yudong; Leng, Jinsong
Abstract: The thermosetting epoxy-based shape memory composite microfibers are successfully fabricated by means of coaxial electrospinning. The PCL/epoxy composite fiber shows core/shell structure, in which epoxy as the core layer is for an enhancing purpose. By incorporating epoxy and PCL, the mechanical strength of composite fibers is greatly reinforced. The deformation is via the heating and cooling process, and the shape memory effect can be demonstrated from the micro level to the macro level. The whole shape recovery performance takes only 6.2 s when triggered by the temperature being at 70 °C. The porosity of woven microfibers changes in response to temperature. In addition, the PCL/epoxy composite microfiber membranes are analyzed in an in vitro cytotoxicity test, which proves that PCL as the shell layer provides the composite microfibers potential capabilities in biomedical science.